Pengaruh Produk Domestik Regional Bruto (PDRB), Belanja Modal dan Jumlah Penduduk Terhadap Penerimaan Pajak Daerah di Kabupaten Banjar - Nicola, Rahmad Nanda; Saleh, Muhammad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to determine the effect of GRDP, capital expenditure, and population on local tax revenues in Banjar Regency and to determine what factors are the most dominant influencing local tax revenues in Banjar Regency. This type of research is quantitative research using secondary time series data. The research location is in the qBanjar Regency, and the data that has been obtained is then carried out with multiple linear regression analysis using SPSS 26. The results of this study indicate that partially, GRDP, capital expenditure, and population have a significant effect on local tax revenues in Banjar Regency, GRDP, spending Capital, and people have a substantial impact on local tax revenues in Banjar Regency and the most dominant variable affecting local tax revenues is population.